Democracia 2.0: La política se introduce en las redes sociales - Caldevilla Domínguez, David (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2010)
Social Networks include groups of people with homogeneous profiles inside heterogeneous network of networks. The paradigm of this universalizing tendency has not gone unnoticed for marketing world, advertising and therefore persuasive communication in all aspects. However, one of the applications that undoubtedly are more appealing and interesting is its recent use in politics world. Many public figures have their blog, their Youtube's Video Channel, their fanpage in popular networks and for that get an automatic informative feedback few seconds after their publication. Are we then facing a much more participatory politics in which the voter is able to give his opinion (which is taken into account) in a matter of seconds, or is it simply a marketing operation in times of crisis to save costs and get closer (and gain) to young voters increasingly accustomed to consuming this type of communication? Anyway, we are facing a new communicative and political landscape that should be analyzed carefully.
Keywords: Politics through Internet; Social networks; Web 2; Spanish political parties; Ciberactivism